Development of worksheets using pop-up books and GeoGebra in the learning of polyhedron concepts - Nuratiqoh; Qohar, Abd (AIP conference proceedings, 2024)
One of the difficulties of studying the polyhedron topics is the visualization of objects so it requires worksheets and learning media that can help students understand the concept of polyhedron. This study aims to develop teaching materials such as worksheets with pop-up book and GeoGebra on learning concepts of polyhedron especially on surface area of cuboids and cubes. This study’s research method is the Plomp development method with three stages: 1) preliminary research; 2) prototyping phase; and 3) assessment phase. The subjects of this study were 23 eight-grade students from the NU Pakis Malang Junior High School in Indonesia. The result showed that the worksheets with pop-up book and GeoGebra on learning concepts of polyhedron had been successfully developed. Experts have validated the worksheets with a score of 3.25, which shows that the worksheets created are valid. The test of practicality obtained from the questionnaire of the students achieved a score of 3.51. The effectiveness test is seen from the results of the test given to students with the results obtained as many as 17 students who complete and 5 students who did not meet the minimum criteria of mastery learning established by the school is 75 so that percentage is 73.95% with effective criteria. These results indicate that the worksheets developed are practical and useful for use in learning mathematical concepts. The results of this study show that other researchers can develop learning concepts of mathematics by using worksheets that uses the learning media as the visualization of objects.